2009
DOI: 10.1080/15287390902929733
|View full text |Cite
|
Sign up to set email alerts
|

Risks to Colombian Amphibian Fauna from Cultivation of Coca (Erythroxylum coca): A Geographical Analysis

Abstract: The Colombian amphibian fauna is among the richest known in the world, with about 20 species of salamanders (order Caudata), 35 of the limbless caecilians (order Gymnophiona), and more than 700 species of frogs and toads (order Anura) recorded from localities within the country. The potential effects of exposure to glyphosate on amphibians arising from production of illegal crops (coca) were examined. The analysis was based on (1) behavior and ecology of species and (2) proximities of actual museum records to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 14 publications
0
10
0
1
Order By: Relevance
“…The tropical and montane rainforest where O. anchicayensis sp. nov. inhabits has been under a relative strong deforestation pressure due to the cultivation of illegal crops (Lynch & Arroyo, ) and the quality of its habitat has rapidly degraded. Therefore, considering that its geographic range is relatively smaller (<800 km 2 ) and the latent risk for its habitat lost, we tentatively designate O. anchicayensis sp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The tropical and montane rainforest where O. anchicayensis sp. nov. inhabits has been under a relative strong deforestation pressure due to the cultivation of illegal crops (Lynch & Arroyo, ) and the quality of its habitat has rapidly degraded. Therefore, considering that its geographic range is relatively smaller (<800 km 2 ) and the latent risk for its habitat lost, we tentatively designate O. anchicayensis sp.…”
Section: Discussionmentioning
confidence: 99%
“…The tropical and montane rainforest where O. anchicayensis sp. nov. inhabits has been under a relative strong deforestation pressure due the cultivation of illegal crops(Lynch and Arroyo 2009) and the quality of its habitat has degraded due the intensive use of agrochemicals. Although the protected National Park Farallones de Cali borders the distribution of this species (south of the Anchicayá river), none of the populations described here inhabits within protected areas by the Colombian government.…”
mentioning
confidence: 99%
“…The Colombian amphibian fauna is among the richest in the world with ∼700 species of anurans documented constituting the most diverse group of amphibians in Colombia [Lynch and Arroyo, ]. Although broad concern exists about the negative impact of Roundup formulations on amphibian populations, only 11 Colombian frog species have been studied for herbicide formulation toxicity [Bernal et al, ].…”
Section: Discussionmentioning
confidence: 99%
“…This clade is characterized by having terrestrial breeding, direct development of terrestrial eggs, and by occupying forested areas [Hedges et al, ]. Lynch and Arroyo [] found 47 terrestrial frog species inhabiting forests within 10 km of coca crops and eradication spraying areas in Colombia. Exposure pathways to aerial eradication spraying include direct contact of spray droplets on the exposed skin or through contact with sprayed surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…While there may be small risks to frogs in unvegetated areas in coca fields that are directly oversprayed, the risks from exposures to other more toxic pesticides used by coca growers are much greater (Brain & Solomon, 2009). When considering the small area of Colombia that is actually sprayed each year (< 0.1% Solomon et al, 2007) and that frogs are not exclusively associated with coca growing (Lynch & Arroyo, 2009), it can be concluded that the Glyphos-Cosmo-Flux mixture as used in Colombia for eradication of coca presents a slight but not ecologically significant risk to larval and terrestrial stages of anurans. (Table 1) is indicated by the size of symbols.…”
Section: Discussionmentioning
confidence: 99%